2001
DOI: 10.1897/1551-5028(2001)020<2303:eowhad>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Hardness and Dissolved Organic Material on Bioavailability of Selected Organic Chemicals

Abstract: The influence of water hardness and dissolved organic matter (DOM) on bioavailability of organic chemicals to Daphnia magna was studied by using benzo[a]pyrene (BaP), pyrene, atrazine, and 3,3',4,4'-tetrachlorobiphenyl (TCB) as model compounds. Two types of DOM were used, namely Lake Kontiolampi, Joensuu, Finland water (KL) and Nordic reference fulvic acid (NoFA) dissolved in artificial freshwater. Binding of the four contaminants by KL DOM decreased with increasing water hardness. Furthermore, increasing hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…The BCFs (total radioactivity) varied only slightly between the treatments ( p > 0.05). Earlier, similar results to those reported here, with insignificant differences in BCFs [24], have been reported, but the opposite also have been found [37,38]. Thus, bioconcentration of pyrene is not so evidently decreased in the presence of DOM, as with certain other PAHs, such as benzo[a]pyrene [24,34,39].…”
Section: Dom Modulating Toxicokinetics Of Pyrene In Daphnia Magnasupporting
confidence: 90%
“…The BCFs (total radioactivity) varied only slightly between the treatments ( p > 0.05). Earlier, similar results to those reported here, with insignificant differences in BCFs [24], have been reported, but the opposite also have been found [37,38]. Thus, bioconcentration of pyrene is not so evidently decreased in the presence of DOM, as with certain other PAHs, such as benzo[a]pyrene [24,34,39].…”
Section: Dom Modulating Toxicokinetics Of Pyrene In Daphnia Magnasupporting
confidence: 90%
“…Some studies showed that increasing water hardness reduced benzo[a]pyrene and pyrene binding to fulvic acids and, at the same time, increased their bioavailability. Moreover, bioconcentration of pyrene and trichlorobenzene increased with increasing water hardness [38]. A significant role also was observed in other studies of sorption properties (cation-exchange capacity) on the toxicity process of bottom deposits in relation to H. incongruens [39].…”
Section: Toxicity Of Sewage Sludges In Relation To Their Propertiessupporting
confidence: 65%
“…It is likely that the [DOC] values for most of the water samples were so small that the eff ect of a given DOM property became indiscernible from the variability imbedded in the calculated K DOC or the measured DOM property. It is also likely that K DOC of pyrethroids in natural surface waters are determined by multiple DOM characteristics, and simple single component regressions are inadequate to fully describe complex variations in K DOC (Schlautman and Morgan, 1993;Kukkonen and Pellinen, 1994;Akkanen and Kukkonen, 2001). Th e characteristics not considered in this study may include the size and weight distribution and compositions of humic substances (Gauthier et al, 1987;Haitzer et al, 1999;Perminova et al, 1999).…”
Section: Water Samples Permethrin Cyfl Uthrinmentioning
confidence: 99%